QUALITE DE VIE ET SANTE DANS UN QUARTIER A HABITAT INDIGNE DE LA VILLE D’ABIDJAN (COTE D’IVOIRE) : ROLE DE L’ASSAINISSEMENT DANS CE DEBAT ECOLOGIQUE - Kaba, Ibrahima (European Scientific Journal, ESJ, 2015)
A survey of safety management, sanitation and diseases linked to poor hygiene was conducted in households of Abobo-Sagbé. This observation combines a collection of qualitative and quantitative data on a workforce of 120 individuals surveyed. At the end of the study, theories describe the sub-district Sagbé as an Unworthy District Space Habitat. This approach follows the assumption that the average health status of a population depends on the level of sanitation and basic infrastructure equipment it enjoys but also its ability to adapt (reactions and practices) in a post-crisis context; Indeed, the health risk in this county is growing day by day, and this article shall expose its determinants from a socio-constructivist approach while allowing to understand deeply the representations of the resident populations on their life quality.